"White‐Out" After Lung Transplantation: A Multicenter Cohort Description of Late Acute Graft Failure. Issue 7 (11th April 2017) - Verleden, S. E.; Gottlieb, J.; Dubbeldam, A.; Verleden, G. M.; Suhling, H.; Welte, T.; Vos, R.; Greer, M.
Abstract : Graft failure represents a leading cause of mortality after organ transplantation. Acute late‐onset graft failure has not been widely reported. The authors describe the demographics, CT imaging–pathology findings, and treatment of patients presenting with the latter. A retrospective review was performed of lung transplant recipients at two large‐volume centers. Acute late‐onset graft failure was defined as sudden onset of bilateral infiltrates with an oxygenation index <200 without identifiable cause or concurrent extrapulmonary organ failure. Laboratory, bronchoalveolar lavage (BAL), radiology, and histology results were assessed. Between 2005 and 2016, 21 patients were identified. Median survival was 19 (IQR 13–36) days post onset. Twelve patients (57%) required intensive care support at onset, 12 (57%) required mechanical ventilation, and 6 (29%) were placed on extracorporeal life support. Blood and BAL analysis revealed elevated neutrophilia, with CT demonstrating diffuse ground‐glass opacities. Transbronchial biopsy samples revealed acute fibrinoid organizing pneumonia (AFOP), organizing pneumonia, and diffuse alveolar damage (DAD). Assessment of explanted lungs confirmed AFOP and DAD but also identified obliterative bronchiolitis. Patients surviving to discharge without redo transplantation (n = 2) subsequently developed restrictive allograft syndrome. This study describes acute late‐onset graft failure in lung allograft recipients, without known cause, which is associated with a dismal prognosis. Abstract : This multicenter study describes epidemiology, pathology, radiology, and treatment of acute late onset graft failure following lung transplantation.